The Effectiveness of Abacus on Quick and Accurate Counting Ability based on Ethnomatematics in Madrasah Ibtidaiyah in Thailand - Prami Shella Meika Anjasrina; Linda Indiyarti Putri; Ma'as Shobirin (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
The research aimed to determine the effectiveness and learning outcomes of using abacus media on the ability to count quickly and accurately based on ethnomatematics in class I MI Saengprathip Wittaya Mulniti School Thailand 2019/2020. This study used a quasi-experimental design with pretest-posttest control group design. The results of statistical analysis showed that using the abacus media had an effect on learning outcomes. This is evidenced by the results of the analysis of the N-gain score test which shows the mean value of the experimental class of 62.12 or 62% which is included in the moderate or moderately effective category. Furthermore, the calculation using the Paired Samples Statistics test states that there is a difference in the average paired sample of the experimental class with a pretest of 72.65 <posttest 90.86, which means that there is a difference in the average pretest and posttest results of the experimental class. Through the results of this study, it is hoped that it will be able to add to the scientific repertoire related to the importance of using ethnomatematic based props.